ترجمة واو الحال إلى الملايوية بين تفسير المربوي وتفسير نور الإحسان وترجمان المستفيد: سورة البقرة نموذجا - Wan Moharani Mohammad; Zulkipli Md. Isa; Nurhasma Muhamad Saad; Farah Nadia Harun; Muhammad Marwan Ismail; Sulaiman Ismail (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia